Davydov Vaginoplasty in Mayer–Rokitansky–Küster–Hauser Syndrome Patient Presenting With Urethral Dilatation - Jurgis Vitols; Lasma Lidaka (Case Reports in Obstetrics and Gynecology)
Conclusion: MRKH patients and healthcare providers should be educated on the damaging consequences of intraurethral intercourse. More cases need to be reported to establish the best treatment options for a normal sexual life.